Unpacking ‘The Night We Met’ How the Song Evokes Varied Emotional Responses from Listeners - Sima Rahil; Abiyyu Alghozy; Tiofany Setya Hadi; Syamsurrijal syamsurrijal (Insan Kreasi Media, 2025)
This article explores how the song The Night We Met by Lord Huron evokes varied emotional responses from listeners through the lens of Saussure’s semiotics. By analyzing the lyrics as signs composed of signifiers (words) and signified (emotional meanings), this study reveals the song's ability to resonate universally across themes of love, memory, and loss. The research employs a qualitative descriptive method, gathering data from listener responses on social media platforms like Instagram, TikTok, and YouTube. The findings indicate that the song elicits diverse emotions, such as nostalgia, longing, and regret, depending on individual interpretations. Through its poignant lyrics and symbolic depth, The Night We Met demonstrates music's capacity to connect deeply with human experiences, making it a powerful medium for emotional expression and reflection.